Pictures, Quotations, and Distinctions : Fourteen Essays in Phenomenology. - Sokolowski, Robert (: Catholic University of America Press, 2022)
One of the major contributions of Husserl's phenomenology has been to show that things present themselves to us in strikingly different ways. There are various kinds of presentations and something like logical structures in them that allow the truth of things to appear. Being pictured is different from being named, and also different from being distinguished from something else. The fourteen essays in this volume provide concrete and colorful examples of strategic forms of presentation, and they also shed light on us as persons who exercise our intelligence when we let things appear in these various ways. Even our moral conduct takes place because something appears to us as to be done or to be avoided in a situation that calls for action. When we quote what someone has said, for example, we express things as they have been expressed by someone else, and we invoke the authority of that other speaker. In measurement, we either bring external units, such as inches or yards, to determine the "how much" of things; or we engage in "internal measurement" and use one part of the object to determine the size of the whole. In moral action, the deep core of what we do involves either benevolence or malevolence, and in such conduct we shape or confirm ourselves as good or bad. Even the timing of things, the measurement of their motions and the determination of their before and after, in both clock and calendar time, cannot take place without the involvement of the person's own interwoven perceptions, remembrances, and anticipations, all held together by the underlying flow of personal as well as worldly temporality. The essays in this book are an attempt to blend the philosophical approaches of Aristotle and Husserl, the classical and the modern, to help us appreciate what Aristotle called "being as the true," and to show how the human person is involved in this enterprise.
Front Matter(pp. i-vi) -- Table of Contents(pp. vii-viii) -- Preface(pp. ix-x) -- Provenance of the Essays(pp. xi-xii) -- Introduction(pp. xiii-xiv) -- 1 Picturing(pp. 3-26) -- 2 Quotation(pp. 27-52) -- II -- 3 Making Distinctions(pp. 55-92) -- 4 Explaining(pp. 93-108) -- III -- 5 Timing(pp. 111-138) -- 6 Measurement(pp. 139-154) -- 7 Exact Science and the World zn Which We Live(pp. 155-170) -- IV -- 8 Exorcising Concepts(pp. 173-186) -- 9 Referring(pp. 187-210) -- V -- 10 Grammar and Thinking(pp. 213-226) -- 11 Tarskian Harmonies in Words and Pictures(pp. 227-242) -- VI -- 12 Moral Thinking(pp. 245-260) -- 13 What Is Moral Action?(pp. 261-276) -- 14 Knowing Natural Law(pp. 277-292) -- Notes(pp. 293-318) -- Index(pp. 319-325).
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Phenomenology; Phénoménologie.; phenomenology; Phenomenology